INTEGRITAS INTERNAL AUDITOR SEBAGAI VARIABEL MODERASI PENGARUH KOMPETENSI, PENGALAMAN KERJA INTERNAL AUDITOR DAN DUKUNGAN MANAJEMEN SENIOR TERHADAP EFEKTIVITAS AUDIT INTERNAL - Sirajuddin, Betri; Ravember, Rafliande (Universitas Muhammadiyah Palembang, 2020)
The goal is to determine the effect of Competence, Work Experience Internal Auditor, and Senior Management Support The Effectiveness of Internal Audit with Integrity Internal Auditor as moderating variable on Public Private Bank Prabumulih. This type of research is associative research. The data used are primary and secondary data. The population is scattered and auditors working in the Public Private Bank Prabumulih total of 32 respondents. Data collection techniques by using interviews and questionnaires. Methods of data analysis used in this research is the analysis of quantitative and qualitative analysis. These results indicate that the competence positively and significantly affects the effectiveness of the Internal Audit, Internal Auditor Work Experience positively and significantly affects the effectiveness of Internal Audit, and Senior Management Support Internal Auditor positively and significantly affect the Effectiveness of Internal Audit. Competence positively and significantly affects the effectiveness of the Internal Audit Integrity moderated Internal Auditor, Work Experience positively and significantly affects the effectiveness of the Internal Audit Integrity moderated Internal Auditor,